Corticopuncture Facilitated Microimplant-Assisted Rapid Palatal Expansion - Selly Sayuri Suzuki; Laila Fernanda Souza Braga; Denise Nami Fujii; Won Moon; Hideo Suzuki (Case Reports in Dentistry)
Introduction. Microimplant-assisted rapid palatal expansion (MARPE) has been considered an alternative to avoid extensive surgical procedures. In order to obtain skeletal results of MARPE, force should be enough to overcome areas of resistance and the first one that is required to be disrupted is the midpalatal suture, which becomes increasingly interdigitated after adolescence. Objective. The present study aimed at providing a novel approach using a minimally invasive method called corticopuncture (CP) in association with MARPE illustrated by a case report of a 35-year-old Brazilian female Caucasian patient presenting maxillary transverse deficiency. Method. Treatment plan started with an orthopedic correction of the transverse problem using a MARPE device. After many unsuccessful attempts to activate MARPE, corticopunctures were performed along the midpalatal suture. CP procedure at the midpalatal suture included 8 perforations (2 mm apart), performed after previous predrilling followed by miniscrew insertion (5 mm thread length and 1.8 mm diameter). Results. After CP and new activation protocol, the opening of the midpalatal suture was observed by CBCT images, showing skeletal results, suture split of 3.14 mm (premolar area) and 2.06 (molar area), an increase of 4.3 mm (premolar) and 3.03 mm (molar) in basal bone width, 4.43 mm (premolar) and 3.1 mm (molar) in cortical bone width, and minimal dental effects (mean of 1.2° of tooth tipping). Conclusion. The combination of MARPE and corticopuncture method was proved to be a nonsurgical treatment option to correct maxillary transverse deficiency in an adult patient. CP was able to weaken suture interdigitation thus facilitating the split.